Response to: the adult multidisciplinary respiratory neuromuscular clinic. Issue 4 (December 2020) - Willis, Tracey; Macfarlane, Mike; Willis, Derek
We read with interest Shah, Murphy and Kaltsakas' article "The adult multidisciplinary respiratory neuromuscular clinic" [1]. The authors recognise the positive support which palliative care services can offer adult patients with neuromuscular disorders (NMD), but also that access to services can be restricted for several potential reasons. The authors suggest that indicators for the introduction of palliative care services in NMD would be helpful. A new "traffic light" system is recommended to identify adult NMD patients who would benefit from advance care planning and possible referral to palliative care services https://bit.ly/3mVDY0P